PERTANGGUNGJAWABAN PIDANA KORPORASI PADA KASUS KEJAHATAN LINGKUNGAN (SINKRONISASI UNDANG-UNDANG NO 40 TAHUN 2007 TENTANG PERSEROAN TERBATAS DENGAN REGULASI PERUNDANG-UNDANGAN LAINNYA YANG MENGATUR TENTANG KEJAHATAN LINGKUNGAN) - Widya Selvia; Erdianto Effendi; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Pollution and environmental damage often occur in a process of development orproduction of a person or corporation. Corporation or limited liability company is a businessentity or legal entity which in its production process is directly related to the environment.For this reason, it is very likely that the production process can result in pollution orenvironmental damage. The purpose of this study was to determine the criminal liability ofcorporations in environmental crime cases and legal arrangements regarding corporatecriminal liability in cases of environmental crime in contributing to the reduction in thenumber of current environmental crime casesThis type of research is normative legal law research that focuses on principles byformulating legal principles, both from social data and from positive written legal data,whereas if seen from the nature of this research is descriptive. This study uses secondarydata, namely data that has been prepared.The results of this study are corporate criminal liability in cases of environmentalcrime based on Law Number 40 of 2007 concerning Limited Liability Companies with otherlegislations that regulate environmental crime, namely: a) corporate managers as makers ofcriminal acts and corporate managers who are responsible criminal; b) the corporation asthe maker of a criminal act, but the corporate management is criminally responsible; c)corporations as makers of criminal acts and corporations that are criminally responsible.The legal regulation regarding corporate criminal liability in cases of environmental crimein contributing to the reduction of the number of cases of current environmental crime isbeing able to prosecute and convict individuals, including administrators or managers,including the corporation itself by paying attention to and adhering to the objectives of socialpolicy. namely protection and welfare of the community so as to reduce the number ofenvironmental crimes.Keywords: criminal liability, corporation.